Ex vivo glucocorticoid receptor-mediated IL-10 response predicts the course of depression severity - von Zimmermann, Claudia; Böhm, Lea; Richter-Schmidinger, Tanja; Kornhuber, Johannes; Lenz, Bernd; Mühle, Christiane (Journal of Neural Transmission, 2021)
Directly measuring hypothalamic pituitary adrenal (HPA) axis function, an important player in affective disorders, is intensive and invasive. A crucial component of this system, the activity of the glucocorticoid receptor (GR), can be assessed ex vivo instead. Here, we investigated GR sensitivity in patients with major depressive disorder (MDD) to determine its predictive potential. Psychometric data and blood samples were collected from patients experiencing a major depressive episode (MDE, n = 87), healthy control subjects (n = 49), and patients with remitted MDD (n = 31) at baseline and (for patients) after median 20 days of follow-up after treatment as usual. Blood cells were stimulated ex vivo with lipopolysaccharide and the effect was suppressed by increasing dexamethasone (DEX) concentrations. The resultant cytokine secretion profile (for IL-6, IL-10, and TNF-α) was considered indicative of GR activity. Higher baseline scores of the Montgomery–Åsberg Depression Rating Scale (MADRS) were associated with a stronger decrease of logIC IL-6 (indicating an increase of GR sensitivity). Higher baseline logEC IL-10 (indicating a lower GR sensitivity) and a stronger reduction of logEC IL-10 (indicating a stronger increase in GR sensitivity) were associated with a stronger decrease in the MADRS score. Patients with remitted MDD showed higher logIC TNF-α values (indicating lower GR sensitivity) in comparison to patients with a current MDD at baseline and follow-up. Initially low GR sensitivity measured ex vivo in peripheral blood cells that increases over the course of treatment could serve as a predictive marker for stronger improvement in depression severity.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Cytokines; Depression; Glucocorticoid receptor; Hypothalamic–pituitary–adrenal axis